Comparative epidemiology of sudden infant death syndrome and sudden intrauterine unexplained death. Issue 2 (1st September 2002) - Frøen, J F; Arnestad, M; Vege, Å; Irgens, L M; Rognum, T O; Saugstad, O D; Stray-Pedersen, B
Abstract : Background: Unexplained antepartum stillbirth and sudden infant death syndrome (SIDS) are major contributors to perinatal and infant mortality in the western world. A relation between them has been suggested. As an equivalent of SIDS, only cases validated by post mortem examination are diagnosed as sudden intrauterine unexplained death (SIUD). Objective: To test the hypothesis that SIDS and SIUD have common risk factors. Methods: Registration comprised all stillbirths in Oslo and all infant deaths in Oslo and the neighbouring county, Akershus, Norway during 1986–1995. Seventy six cases of SIUD and 78 of SIDS were found, along with 582 random controls surviving infancy, all singletons. Odds ratios were obtained by multiple logistic regression analysis. Results: Whereas SIUD was associated with high maternal age, overweight/obesity, smoking, and low education, SIDS was associated with low maternal age, smoking, male sex, multiparity, proteinuria during pregnancy, and fundal height exceeding +2 SD. Thus the effects of maternal age were opposite in SIUD and SIDS (adjusted odds ratio 1.39 (95% confidence interval 1.17 to 1.66) per year, p < 0.0005). Heavy smoking, male sex, and a multiparous mother was less likely in SIUD than in SIDS (0.22 (0.06 to 0.83), 0.22 (0.07 to 0.78), and 0.03 (<0.01 to 0.17) respectively). Overweight/obesity and low fundal height were more common in SIUD than in SIDS (7.45 (1.49 to 37.3) and 13.8 (1.56 to 122) respectively). Conclusions: The differences in risk factors do not support the hypothesis that SIDS and SIUD have similar determinants in maternal or fetal characteristics detectable by basic antenatal care.